Bridging organization design and performance : - Kesler, Gregory (John Wiley & Sons, Inc., 2016)
Bridging Organization Design and Performance is a handbook for leaders looking to enhance the success of their organizations and themselves. Companies that compete globally require organizational operating models as robust as their strategies. Many companies have created elegant designs and consider their worldwide, matrix organizations sources of competitive advantage. However, the reality is that these complex structures bring many challenges and senior executives are often frustrated by the difficulties of delivering growth in organizations that span numerous brands, products, and geographic regions.